Pengaruh Financing To Deposit Ratio (Fdr), Non Performing Financing (Npf) Dan Capital Adequacy Ratio (Car) Terhadap Profitabilitas (Roa) Perbankan Syariah Di Indonesia - Riduwan Riduwan (Universitas Muhammadiyah Surabaya, 2021)
This study aims to analyze the influence of Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Capital Adequacy Ratio (CAR) on Profitability of Islamic Banking in Indonesia which is proxied by Return On Assets (ROA). This research is quantitative research. the population used is the annual report of all Sharia Commercial Banks in Indonesia during period 2014-2018. The Sample chosen used a purposive sampling method and the sample obtained of 6 Islamic Banks. In this research the analysis used was multiple linear regression analysis using IBM Statistics version 21 software. Based on the results of multiple linear regression from this study showed that simultaneously the dependent variable (ROA) can be explained by the independent variable consisting of FDR, NPF, and CAR. Partially, the NPF variable has a negative and significant effect on ROA. While the FDR and CAR variables have a positive and not significant effect on ROA. Keyword: ROA, FDR, NPF, CAR